Kadar Debu terhadap Kapasitas Vital Paru pada Masyarakat di Sekitar PT Semen Baturaja - Sri Indra Trigunarso; Prayudhy Yushananta; Fernanda Kurnun Ainin (Politeknik Kesehatan Tanjung Karang, 2018)
Function disorders were generally occurred due to individual factors and environmental factors. One of the industries that experienced a lot of development was PT. Semen Batu Raja which is located in Kelurahan Way Lunik. Dust particles with a size of fewer than 50 microns that normally fly can enter the workers' respiratory tract by being sucked in during breathing (ILO, 1998). Public Health Center of Way Lunik mentioned that the prevalence of ARI that occurred during 2016 amounted to 243 cases. The purpose of this study was to determine the relationship of cement dust levels to vital lung capacity in the community around PT. Semen Batu Raja in 2017. The research method was cross-sectional design. Independent variable was humidity of the house, room temperature, ventilation, smoking habits, gender, age, length of stay, and knowledge. While the dependent variable was lung vital capacity. Based on the results of the study, of the 145 Panjang community respondents around PT. Semen Batu Raja obtained 82 respondents who were diagnosed with pulmonary function disorders. Factors that have a significant influence to pulmonary function disorders were ambient dust levels with mean value 171.5 µg / Nm3 (0.025), home ventilation with mean value ≥ 10% (0.041) and smoking history of respondents with the greatest risk was active smokers. Other factors that were not statistically related were house humidity (0.041) mean 63.2%, house temperature (0.654) mean 29.5⁰C, gender, length of stay (0.82), and knowledge (0.654) This study is expected to be reference studies and studies for several parties.